Aspectos psicológicos relacionados con la cirugía de reducción de riesgo - Costa, Gemma; Gil, Francisco Luis (Psicooncología, 2005)
The main objective of this paper is to review the psychological effects of the risk reduction surgery (mastectomy and ooforectomy) in BRCA carriers. This option reduce the risk to develop breast and ovarian cancer in BRCA carriers, but we don?t know if these two therapeutic approaches can increase the survival in this risk women group. We need news prospectives studies to clarify the efficacy of this prophylactic surgery.